Obedience Dan Attitude of Hospital Employees on Non-Smoking Area Policy in Jombang - Nuswantara; Wahyuni, Chatarina Umbul; Hargono, Arief; Martini, Santi; Christanto, Daniel (Universitas Muhammadiyah Surakarta, 2023)
Introduction: Hospital employees are expected to be role models for the surrounding community in obeying the Non-Smoking Area (NSA) policy. However, in reality, only some of the hospital employees in Jombang obey it. Cigarette ashes are still found in many hospitals' hidden corners. This study aims to analyze the attitude and obedience of hospital employees in Jombang to ward NSA policy in hospitals. Method: This research is an analytic descriptive with a cross-sectional study approach. Random sampling collected data using a Google form questionnaire on 56 male employees. Analysis was conducted by counting the frequency distribution of employees' NSA policy comprehension variable, the dangers of smoking variable, the attitudes toward smoking variable, and the last obedience towards NSA variable. Result: It showed that 92.9% of employees are aware of NSA policy, 98.2% are aware of the dangers of smoking, yet 19.6% of the employees are smokers, and 100% of the smoking employees have ever smoked in a hospital. PR univariate calculations show that comprehension of the danger of smoking has NSA policy has risked the dangers of smoking 2.7 times in the hospital. Meanwhile, employees' comprehension of NSA policy is a risk factor. The employees who understand NSA policy have the risk of 2,889 times smoking in the hospital. Conclusion: Employees are aware of NSA policy and the dangers of smoking to their health. Nevertheless, some employees smoke in the hospital due to addiction. Efforts have been made. Include: increasing education, monitoring from colleagues, and CCTV monitoring in locations frequently used by smoke.